2010
DOI: 10.1111/j.1365-2702.2009.03168.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin injuries caused by medical adhesive tape in older people and associated factors

Abstract: Skin care to minimise contamination and more effective ways of applying medical adhesive tape may be needed to prevent contact dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 8 publications
2
47
1
3
Order By: Relevance
“…We also confirmed that a pure resin sample exhibits no thermal peak in the temperature range from 25 to 125 Both exothermic 73.8 and endothermic peaks 96. 5 appeared in the thermogram of the meltquenched in-resin CER sample Fig. 2 a .…”
Section: Differential Scanning Calorimetrymentioning
confidence: 97%
See 1 more Smart Citation
“…We also confirmed that a pure resin sample exhibits no thermal peak in the temperature range from 25 to 125 Both exothermic 73.8 and endothermic peaks 96. 5 appeared in the thermogram of the meltquenched in-resin CER sample Fig. 2 a .…”
Section: Differential Scanning Calorimetrymentioning
confidence: 97%
“…In addition, the following problem has emerged: physical stimulation by frequent application and removal of stoma appliances can damage skin. This skin damage, which is mainly due to the removal of the epidermal layer of the skin 5 , is a more serious problem than allergic dermatitis for stoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…In one prospective cohort study of older individuals admitted to a long-term care facility, the cumulative incidence of skin injury caused by adhesive tape was reported to be 15.5% (incident density 38 per 1000 person days). 27 Clinical manifestations of MARSI observed in this study included contact dermatitis (71%), trauma (21%), and infection (9%). The use of adhesives was also identified as the primary cause of skin breakdown among neonatal intensive care unit patients in a nursing research utilization project involving 2820 newborns.…”
Section: Medical Adhesiveyrelated Skin Injurymentioning
confidence: 97%
“…Medical adhesive products are a common cause of nonallergic irritant contact dermatitis, 10,27,44 and such reactions are more likely to occur with extended exposure. 10 Allergic contact dermatitis related to adhesive products occurs much less frequently than irritant contact dermatitis, although numerous case reports of allergic reactions to components of adhesive products can be found in the literature.…”
Section: Assessmentvallergy/sensitivitymentioning
confidence: 99%
“…Patients considered at risk for facial skin injuries in adults include the elderly [8, 24, 25], those with increased skin fragility such as patients on chronic steroid treatment or those having undergone skin resurfacing procedures or using prescription exfoliating agents [9, 16], also in the prone position [7, 26] or prolonged tape duration [27]. …”
Section: Introductionmentioning
confidence: 99%